Fighting Money Politics and Shamanic Practices - Tjahjoko, Guno Tri (Jurnal Politik, 2020)
This study aims to describe the efforts of female candidates to break the practice of money politics and the influence of shamans in the 2018 Sriharjo subdistrict election (pilkades). The author used qualitative methods with a case study of the Sriharjo village-head election in Bantul Regency. The author collected primary data through interviews, in-depth group discussions, and observations. Secondary data were collected through a literature review, online articles, photos, and video studies of the pilkades process. The findings of this study show the practice of money politics carried out by “snipers,” whose job is to distribute envelopes containing money from house to house from night to dawn one day prior to election day. In addition, candidates also provide assistance and facilities to the community to get their votes. The success team also uses the services of shamans by spreading flowers in certain areas with the aim of spiritually binding people so as not to vote for other candidates. Responding to the competitor’s strategy, the female candidate employed the politics of conscience to empower the community, monitored the snipers of other candidates, built networks, and broke the spiritual powers.